2020
DOI: 10.1177/2325967120957646
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Frontal Plane Angles Used to Predict ACL Strain and Identify Those at High Risk for Sports-Related ACL Injury

Abstract: Background: Knee abduction moment during landing has been associated with anterior cruciate ligament (ACL) injury. However, accurately capturing this measurement is expensive and technically rigorous. Less complex variables that lend themselves to easier clinical integration are desirable. Purpose: To corroborate in vitro cadaveric simulation and in vivo knee abduction angles from landing tasks to allow for estimation of ACL strain in live participants during a landing task. Study Design: Descriptive laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…These findings are in line with previous studies which focused on either gait or countermovements [22,38]. The evaluation of frontal plane angles is crucial in the assessment of ACL injury risk and RTS [39,40]. Primary attention is paid to knee and hip frontal plane kinematics.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with previous studies which focused on either gait or countermovements [22,38]. The evaluation of frontal plane angles is crucial in the assessment of ACL injury risk and RTS [39,40]. Primary attention is paid to knee and hip frontal plane kinematics.…”
Section: Discussionsupporting
confidence: 89%
“…Knee abduction angle during DVJ is a predictor of ACL injury. 3 , 25 The present study confirmed that athletes with a high knee abduction angle have higher ACL strain during the DVJ. Note that this study does not prove a single effect of knee abduction angle but rather that other featured biomechanical variables are linked in high ACL strain trials.…”
Section: Methodssupporting
confidence: 85%
“…While ACL strain is influenced by multiplane loading, 14 , 29 , 33 knee abduction moment during landing is a predictor of ACL injury, and it increases ACL strain in cadaveric simulations. 2 5 , 25 , 46 , 47 , 50 A recent musculoskeletal modeling study demonstrated that knee abduction moment was larger during landing in the frontal plane, with higher vertical and lateral ground-reaction force, lower gluteus medius force, and a laterally shifted and tilted pelvic position. 51 This musculoskeletal modeling study 51 supported a previously proposed ACL injury mechanism in frontal plane mechanics.…”
mentioning
confidence: 99%
“…The model may have improved accuracy with addition of other joint moments (eg, hip or ankle) or joint kinematics. 7 However, the performance of the discriminant analysis was good to excellent even with the current data set, with accurate prediction of 94.1% of injuries, a 4.7 times increase from chance. Future application of an artificial neural network machine learning algorithm would be valuable to assess these data; however, because this data set was limited to 41 injury events, more outcomes would be needed to properly validate the constructed model after algorithm training.…”
Section: Discussionmentioning
confidence: 71%